THE IMPORTANCE AND THE ROLE OF THE POLYGON IN THE DEVELOPMENT OF BIOMOTORING EXPERIENCES OF THE FIRST SERIES OF NINE YEARS LASTED ELEMENTARY SCHOOL STUDENTS - Drago Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
In order to underline the importance of the polygon for the students of the first series of nine years lasted school in the function of development, escort and control of the elementary monitoring experiences, in the sense of space solution, simple obstacles, certain level of resistance and the objects manipulation, the most suitable models of polygons were suggested, adapted to the characteristics and abilities of the adult students populationThe polygons, important in organizational sense-methodical forms of working, induced the interest of the students for activity in this sense of: - the high students motivation and setting (creating) of polygon; - the simplicity of performing, completely understanding, ideas and closeness of the antropology characteristics of this age students; - the use of the complex of the exercises which has the great influene on the development of the whole students' organism; - the inhencing on the higher level of the upbringing function in the teaching process (discipline, self-proofing, wish to be more successful, social aims and intensions of the teaching process, education, correlation with other fields).